Unions and Pay Equity Bargaining in Canada - Hart, Susan (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2002)
SummaryProvincial government pay equity policies require the negotiation of pay equity in unionized workplaces. The methodology is complex and unions have to be knowledgeable and committed to rectifying discriminatory wages. According to the literature, Canadian unions have shown varied levels of effectiveness regarding their pursuit of women’s equality, and this article explores how well these unions represent women’s interests during pay equity bargaining. Based on case studies of the Ontario public service and health care in Newfoundland, the article concludes that the most effective unions supplemented their conventional negotiating techniques with gender analysis and pay equity expertise. These tools were developed primarily through negotiators’ formal links with internal equality structures and their knowledge of equality policies, together with women’s networking inside and outside the labour movement.